The effect of media mind mapping On the ability to write narrative text - Harahap, Olivia Feby Mon; Nasution, Nurul Hidayah (Universitas Aufa Royhan, 2018)
The aim of this study is to increase students there is The effect of media mind mapping on the ability to write narrative text at the grade tenth students of SMA N 6 Padangsidimpuan. The method of this research is experimental method. The population of research is 320 respondents and the sample of the research with the cluster sampling of six classes. While the samples taken were 38 students by voting each class. after being voting out as a sample class X-6. To get the results of this study the writer compared the mean pretreatment using media mind mapping and after using media mind mapping in learning to write Narrative Texts. After carrying out the collection and analysis of the score of the ability to write Narrative Text before using media mind mapping the mean was found to be 64.21. If converted to predetermined ability criteria, the mean includes the criteria for 'less'. Learning completeness reaches 65.79% or has not achieved minimal completeness classically as expected, namely a minimum of 75%. While the mean test results of the ability to write Narrative Text after using mind mapping media amounted to 82.63. The mean is included as a good criterion, while the entire sample is declared complete learning. Based on the statistical calculation obtained tcount is 12.61. The amount of data is 38 so db = 38-1 = 37. For t 0.95% there is no distribution for N 37, which is found is t table for N 30 of 1.70 and N 40 of 1.68. Thus for N 37 is 1.70 + 1.68: 2 = 1.69. Ho is tcount > 1.69. Because tcount > t tabel if Ho is rejected or in other words it can be said that the hypothesis reads: there is an influence of media mind mapping on the ability to write Narrative Texts in class X of SMA Negeri 6 Padangsisimpuan accepted the truth. Whereas the null hypothesis reads: there is no effect of media mind mapping on the ability to write Narrative Texts in class X of the Padangsisimpuan Public High School 6 rejected because it is not proven.